Early clinical sequelae of Ebola virus disease in Sierra Leone: a cross-sectional study. Issue 3 (March 2016) - Mattia, John G; Vandy, Mathew J; Chang, Joyce C; Platt, Devin E; Dierberg, Kerry; Bausch, Daniel G; Brooks, Tim; Conteh, Sampha; Crozier, Ian; Fowler, Robert A; Kamara, Amadu P; Kang, Cindy; et al.
Summary: Background: Limited data are available on the prevalence and predictors of clinical sequelae in survivors of Ebola virus disease (EVD). The EVD Survivor Clinic in Port Loko, Sierra Leone, has provided clinical care for 603 of 661 survivors living in the district. We did a cross-sectional study to describe the prevalence, nature, and predictors of three key EVD sequelae (ocular, auditory, and articular) in this cohort of EVD survivors. Methods: We reviewed available clinical and laboratory records of consecutive patients assessed in the clinic between March 7, 2015, and April 24, 2015. We used univariate and multiple logistic regression to examine clinical and laboratory features of acute EVD with the following outcomes in convalescence: new ocular symptoms, uveitis, auditory symptoms, and arthralgias. Findings: Among 277 survivors (59% female), median age was 29 years (IQR 20–36) and median time from discharge from an EVD treatment facility to first survivor clinic visit was 121 days (82–151). Clinical sequelae were common, including arthralgias (n=210, 76%), new ocular symptoms (n=167, 60%), uveitis (n=50, 18%), and auditory symptoms (n=67, 24%). Higher Ebola viral load at acute EVD presentation (as shown by lower cycle thresholds on real-time RT-PCR testing) was independently associated with uveitis (adjusted odds ratio [aOR] 3·33, 95% CI 1·87–5·91, for every five-point decrease in cycle threshold) and with new ocular symptoms or ocular diagnoses (aOR 3·04, 95% CI 1·87–4·94). Interpretation: Clinical sequelae during early EVD convalescence are common and sometimes sight threatening. These findings underscore the need for early clinical follow-up of survivors of EVD and urgent provision of ocular care as part of health systems strengthening in EVD-affected west African countries. Funding: Canadian Institutes of Health Research.